Analysis and Visualization of Sports Performance Anxiety in Tennis Matches - Pokharel, Shiraj; Zhu, Ying (Advances in Visual Computing, 2018)
According to sports psychology, anxiety has a big impact on an athlete’s performance in a sport event. Although much work has been done in sports data analysis and visualization, analysis of anxiety has rarely been included in previous work. In this paper, we propose a method to analyze a tennis player’s anxiety level during a tennis match. This method is based on the psychological theories of anxiety and a database of over 4,000 professional tennis matches. In our model, an athlete’s anxiety level is based on three factors: uncertainty, anticipation, and threat. We have also developed data visualizations to help users study the potential correlation between a tennis player’s anxiety level and his/her skilled performance, such as unforced errors, forced errors, winners, serve directions, first-serve faults, and double faults.